ANALISIS KOMUNIKASI DIGITAL PADA AKSI KEKERASAN VERBAL KOMUNITAS MOBILE LEGENDS SQUADS PROJECT TRV DIKOTA BATAM - Mangara, James Nathan; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2023)
Since the beginning of human civilization, communication has been crucial in exchanginginformation among individuals, groups, and nations. Digital communication, such as textmessaging, voice calls, emails, social media, and in-game instant messaging applications likeMobile Legends, facilitates real-time symbolic interactions across the globe. While providingbenefits, the use of these new media has also led to a decline in societal values and norms,including the emergence of verbal violence in digital communication, involving demeaning,insulting, or threatening language directed towards individuals or groups.This research aims touncover the issue of verbal violence in digital communication. The study involves the MobileLegends Squads Project TRV Community in the City. The researcher employs data collectiontechniques such as interviews and observation, and the findings reveal that digital communicationwithin gaming groups like "Mobile Legends" influences group dynamics and the well-being of itsmembers. Verbal violence in this game has negative impacts, and the moderators of the "MobileLegends" gaming groups play a crucial role in upholding communication ethics and handlingconflicts